2017
DOI: 10.1002/14651858.cd012158.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic lung volume reduction procedures for chronic obstructive pulmonary disease

Abstract: Results for selected BLVR procedures indicate they can provide significant and clinically meaningful short-term (up to one year) improvements in health outcomes, but this was at the expense of increased adverse events. The currently available evidence is not sufficient to assess the effect of BLVR procedures on mortality. These findings are limited by the lack of long-term follow-up data, limited availability of cost-effectiveness data, significant heterogeneity in results, presence of skew and high CIs, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 177 publications
(1 reference statement)
0
25
0
2
Order By: Relevance
“…Additional improvements in lung function were found, including a decrease in RV, improvement in FVC and reduction of RV/TLC ratio, although these end points were less commonly reported (5). No significant difference in TLC was found, and DLCO values were not reported.…”
Section: Coilsmentioning
confidence: 86%
See 2 more Smart Citations
“…Additional improvements in lung function were found, including a decrease in RV, improvement in FVC and reduction of RV/TLC ratio, although these end points were less commonly reported (5). No significant difference in TLC was found, and DLCO values were not reported.…”
Section: Coilsmentioning
confidence: 86%
“…There was no difference in DLCO (5). Whereas in one study the number of adverse events was higher for participants in the intervention group [OR 3.41 (1.48-7.84)] (5), including COPD exacerbations, respiratory failure, pneumonia and bronchospasm, the Ninane study (14) showed no significant difference in adverse events.…”
Section: Intrabronchial Valves (Ibv)mentioning
confidence: 91%
See 1 more Smart Citation
“…On the contrary, endobronchial valve therapy is not useful in patients with lack of fissure integrity or if interlobar collateral ventilation is present. Overall, it seems that these procedures can improve clinical health outcomes, although with a non-negligible rate of adverse events [51].…”
Section: Disease Managementmentioning
confidence: 99%
“…Внедрённая в клиническую практику методика кла-панной бронхоблокации, которая активно исполь-зуется во фтизиохирургии для лечения пациентов с хронической обструктивной болезнью лёгких, при-меняется и в практике торакальных отделений [2,3,5,6,11,13,14,15,16,17].…”
Section: Introductionunclassified